PENDEKATAN STUDI KASUS DALAM PENGAJARAN BAHASA ASING– SEBUAH TINJAUAN PUSTAKA - Roswani Siregar; Heni Subagiharti; Diah Syafitri Handayani; Ahmad Laut Hasibuan; Sutarno Sutarno (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
The aim of this article is to provide general theoretical information regarding the case study approach and present a step-by-step overview of the use of case studies by ESP practitioners. The steps for using case study learning include case discussion, solution finding, feedback, and class discussion. The use of case studies produces great benefits for students in improving foreign language skills. However, there are difficulties in its use, namely designing case studies is a time and energy consuming process. The benefits gained from using case studies in ESP teaching depend on the material covered. Topics that are relevant to knowledge of scientific disciplines will be more interesting to students because they are relevant to the field of science they are involved in. During case study learning, students read cases (reading), listen to each other during group work (listening), present arguments/findings/solutions (speaking), can also provide written analysis of a case (writing), and interact with friends. the group and other students (interaction). Case studies can improve language skills in an integrated manner for students which allows simultaneous use of five language skills, so that this learning method can become an option in teaching foreign languages at the tertiary level